Determination of Heavy Metals Contents of Some Monofloral Honey Produced in Turkey - Tuba Pehlivan, Aziz Gül (Journal of Applied Pharmaceutical Science, 2015)
In the present work, some element contents (Cd, Se, Cr, Pb, Cu, Mn, Ni, Zn, Fe) of 23 different monofloral honey samples from different regions of Turkey were assessed. Origins of monofloral honey research materials are as follows; Pimpinella sp., Castanea sp., Astragalus sp., Onobrychis sp., Mentha sp., Coridothymus capitatus, Robinia pseudoacacia, Cedrus libani, Gossypium sp., Thymus sp., Euphorbia sp., Tilia sp., Eucalyptus sp., Ferula sp., Centaurea solstitialis, Petroselinum sp., Vitexagnus-castus, Helianthus annuus, Citrus sp., Pinus sp., Rhododendron sp., Arbutus sp., Ceratonia siliqua. Metal contents of samples were determined by wet combustion method in ASS machine. As a result of the study, heavy metal contents of honey samples were as follows; Cd
Keywords: Monofloral, Honey, Heavy metal, Turkey.